Elucidating the Feammox nitrogen transformation pathway: Key intermediates and putative multi-species metabolic cooperation in a long-term Feammox-dominant system - Shiyong Zhang; Xiuhong Liu; Rong Cheng; Chenduo Huang; Zhipeng Zhang; Simiao Long; Qing Yang (Water Research, 2026)

Emission characteristics and diffusion simulation of aldehyde-ketone odor gases in wastewater treatment plants with different treatment processes - Linlin Ma; Xiancong Jiang; Yuxuan Song; Simiao Long; Qing Yang (Journal of Environmental Chemical Engineering, 2025)

Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Xiaobo Yan; Simiao Pan; Zhihao Li; Xiaohui Dong; Beiping Tan; Shuisheng Long; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu ) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with L. pentosus at 1.0×10 7 , 1.0×10 8 , 1.0×10 9 CFU/g, respectively. Five kinds of diets were fed to hybrid grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results showed that (1) consumption of OFO diet significantly increased muscle crude lipid, total cholesterol, and total monounsaturated fatty acids contents and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper ( p < 0.05), whereas the addition of L. pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels, increased muscle crude protein content, and enhanced muscle hardness, gumminess, and chewiness compared with FFO or OFO group ( p < 0.05). (2) In addition, ingestion of OFO diet significantly increased muscle phenylalanine content and significantly decreased aspartic acid content ( p < 0.05), while the addition of L. pentosus restored aspartic acid to the level not significantly different from that of FFO group ( p > 0.05). The addition of L. pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine, and alanine content compared to FFO group at the same time ( p < 0.05). (3) Furthermore, the intake of OFO diet would lead to deterioration in muscle flavor quality and increase in noxious odors in grouper, and the addition of L. pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly downregulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system ( p < 0.05), which was protected against by the potent antioxidant properties of L. pentosus . We recommend the supplementation level of L. pentosus to be 1.0×10 9 CFU/g under the highly oxidized conditions of the present trial fish oil.

The Effect of Oxidized Fish Oil on the Spleen Index, Antioxidant Activity, Histology and Transcriptome in Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) - Shuisheng Long; Zhihao Li; Xiaohui Dong; Xiaobo Yan; Hao Liu; Beiping Tan; Shuang Zhang; Simiao Pan; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2021)
The spleen is an important organ in the immune function of fish, and it is also important for hematogenesis and antibody and granulocyte production. However, the effect of oxidized fish oil on the spleen of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) is unknown. In this study, hybrid groupers were fed with oxidized fish oil and the spleen index, antioxidant ability, histology and transcriptome were investigated. Oxidized fish oil did not affect the spleen index. Levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) in the spleen were significantly increased as the amount of oxidized fish oil in the diet increased, but the vitamin E concentration was significantly decreased. The morphological organization of the spleen was damaged with increased oxidative stress. And the spleen reacted to oxidative stress by platelet activation, FOXO and notch signaling pathways, which involved amyloid beta precursor protein binding family B member 1 interacting protein (APBB1IP) gene, glucose-6-phosphatase (G6PC) gene, histone acetyltransferase p300 (EP300) gene, insulin gene and notch 2 gene. In conclusion, the oxidized fish oil caused oxidative stress and damaged its structure. Additionally, oxidized fish oil changed the transcription profile of the spleen.